Structural Analysis of Northwest Sabah Basin by 2D Reconstruction of Seismic Sections - Muhamad Sidek, Mohd Akhmal Bin; Hamzah, Umar (Journal of Geoscience, Engineering, Environment, and Technology, 2018)
The tectonic evolution of thrust fold belt and thrust sheet zone in Northwest Sabah basin was described based on balanced reconstruction of seismic sections representing Mid-Miocene to Recent deposits. The study area is located at the center of a wide crustal deformational zone bordered by the Sunda Shelf on the northeast, Sulu Sea in the southwest and the South China Sea in the northwest. Balancing cross section can be applied after the deformed geological structure geometry is accurately determined from seismic sections and 7 seismic stratigraphic unit from 15 Ma until Recent is consecutively restored. There are four steps involved in retro-deformation processes beginning with removing all faults displacements followed by unfolding the folds, isostasy correction and finally the removal of each compacted layer parts or decomposition. Wider fold wavelengths with least thrust faults were observed from south to north in the seismic sections ranging from 12 to 4 km with an average of about 7 km, while smaller fold wavelengths and more thrust faults were observed in the north based on the same seismic sections. In general, the reconstructed cross sections revealed compressional tectonic deformation activity as shown by shortening strain trending NW-SE. Measurement of total shortening shows that thrust fold belt is imbalance by an exceeds of 14.7 km and more active compared to thrust sheet zone which has only 0.9 km. Results of the study also indicate facies destruction due to shortening which is decreasing towards Pliocene or younger deposits.